2022
DOI: 10.3390/su14020754
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Relations between Cultural Ecosystem Services, Physical Landscape Features and Accessibility in Central-Eastern Europe: A PPGIS Empirical Study from Hungary

Abstract: Despite the growing quantity of ecosystem-services-related research, there is still a lack of deeper understanding on cultural ecosystem services (CES). This is mainly due to the perception of CES, which can vary by geographic location and population. In this study, we present a Public Participation Geographic Information System (PPGIS) method in a Hungarian microregion. Our goal is to increase understanding on how cultural services are perceived in this geographical context and level, and how this relative im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…The calculation of Friedman's statistic, which is represented by χ_r^2, is possible using the following relations and can be done in two ways: (1) where SSbr is the sum of the rank squares between the distributions and k is the number of categories or distributions for which the ranking is done (2) where N is the number of subjects, k is the number of categories or distributions for which ranking is done, and Tg is the sum of the ranks of the g-th group. The value of SSbr is also obtained from the following relation: (3) This test was used to check whether the criteria of satisfaction with time participation are significantly different from each other or not. The results of this test showed that the proposed factors have a significant difference at the 99% confidence level.…”
Section: -Project Information Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…The calculation of Friedman's statistic, which is represented by χ_r^2, is possible using the following relations and can be done in two ways: (1) where SSbr is the sum of the rank squares between the distributions and k is the number of categories or distributions for which the ranking is done (2) where N is the number of subjects, k is the number of categories or distributions for which ranking is done, and Tg is the sum of the ranks of the g-th group. The value of SSbr is also obtained from the following relation: (3) This test was used to check whether the criteria of satisfaction with time participation are significantly different from each other or not. The results of this test showed that the proposed factors have a significant difference at the 99% confidence level.…”
Section: -Project Information Managementmentioning
confidence: 99%
“…Today, in the comprehensive planning and development of cities, important and complex decisions are mandatory for every community and local government or municipality. In this regard, it should be said that making optimal decisions by integrating and combining a set of emerging phenomena such as geographic information system or GIS, which itself is a result of participation, has played a significant role in the flourishing of knowledge and information [2,3]. In recent decades, "urbanization", "sustainable development" and "information and communication technology revolution", as the most important global trends, have played the greatest role in the life of human societies [4].…”
Section: Introductionmentioning
confidence: 99%
“…Thanks to the many disciplines dealing with CES, their meaning and interpretation differ according to geographical location, as well as socio-cultural and professional background [3,5,6]. Following the same line, several classifications exist, but the most commonly used are the following categories: spiritual and religious, recreation and ecotourism, aesthetic, inspirational, educational, a sense of place, and cultural heritage.…”
Section: Introductionmentioning
confidence: 99%
“…Today, in the comprehensive planning and development of cities, important and complex decisions are mandatory for every community and local government or municipality. In this regard, it should be said that making optimal decisions by integrating and combining a set of emerging phenomena such as geographic information system or GIS, which itself is a result of participation, has played a significant role in the flourishing of knowledge and information (Johnson et al, 2022;Valánszki et al, 2022). Living in a world without a desk might be tough, but managing a world without time seems remarkably disastrous.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, whether PGIS is correct or PPGIS just wastes its time and deals with a completely marginal matter, and we move away from the goal and make a system with this historical identity that was created to support the marginalized strata ineffective (Radil and Anderson, 2018;Dunn, 2007).Today, in the comprehensive planning and development of cities, important and complex decisions are mandatory for every community and local government or municipality. In this regard, it should be said that making optimal decisions by integrating and combining a set of emerging phenomena such as geographic information system or GIS, which itself is a result of participation, has played a significant role in the flourishing of knowledge and information (Johnson et al, 2022;Valánszki et al, 2022).…”
Section: Introductionmentioning
confidence: 99%